Pelatihan Dan Pendampingan Desain Kemasan untuk Meningkatkan Branding Produk UMKM Desa Manggihan Kecamatan Getasan Kabupaten Semarang - Aji Supriyanto; Mohammad Riza Radyanto; M.G Kentris Indarti (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Manggihan Village, Getasan District, Semarang Regency, which is at the foot of Mount Merbabu, is close to the Kopeng tourist destination area. This village has a population that has professional business owners in the Micro, Small, and Medium Enterprises (MSME) category in the culinary sector which makes cracker rambak, processed dry food with various types of chips And processed catfish food. The problem faced in their business is that they do not yet have a product identity in the packaging such as sticker labels, packaging that attracts potential buyers, so the message of the product has not been conveyed. This community service activity aims to provide knowledge and awareness for MSMEs about the importance of product packaging that attracts potential buyers thereby providing added value and competitive advantage for the products produced. The method used in this service is holding socialization activities on the importance of product branding, training, and assistance in making sticker labels and food product packaging design. In the mentoring process, a needs analysis is first carried out including the type of packaging material, packaging shape, packaging identity color, and product logo. It is hoped that the output targets that will be achieved through this program will help partner MSMEs increase the amount of income from sales by using new packaging and product logos designed in such a way that they are attractive to buyers. The product packaging and labels produced as the output of this activity can become an identity. a typical Manggihan Village product that differentiates it from similar products in other areas